RNA-binding protein ZFP36L1 regulates osteoarthritis by modulating members of the heat shock protein 70 family - Son, Young-Ok (Nat Commun, 2019)
Osteoarthritis (OA) is a whole-joint disease characterized by cartilage destruction and other whole-joint pathological changes. There is currently no effective disease-modifying therapy. Here we investigate the post-transcriptional mRNA regulation of OA-modulating proteins in chondrocytes and show that the ZFP36 family member, ZFP36L1, is specifically upregulated in OA chondrocytes and OA cartilage of humans and mice. Adenovirus-mediated overexpression of ZFP36L1 alone in mouse knee-joint tissue does not modulate OA pathogenesis. However, genetic ablation or silencing of Zfp36l1 significantly abrogates experimental OA in mice. Knockdown of Zfp36l1 increases the mRNA expression of two heat shock protein 70 (HSP70) family members, which act as its direct targets. Furthermore, overexpression of HSPA1A in joint tissues protects mice against experimental OA by inhibiting chondrocyte apoptosis. Our results indicate that the RNA-binding protein, ZFP36L1, regulates HSP70 family members that appear to protect against OA pathogenesis by inhibiting chondrocyte apoptosis.